2016
DOI: 10.1093/molbev/msw035
|View full text |Cite
|
Sign up to set email alerts
|

Large-Effect Beneficial Synonymous Mutations Mediate Rapid and Parallel Adaptation in a Bacterium

Abstract: Contrary to previous understanding, recent evidence indicates that synonymous codon changes may sometimes face strong selection. However, it remains difficult to generalize the nature, strength, and mechanism(s) of such selection. Previously, we showed that synonymous variants of a key enzyme-coding gene (fae) of Methylobacterium extorquens AM1 decreased enzyme production and reduced fitness dramatically. We now show that during laboratory evolution, these variants rapidly regained fitness via parallel yet var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 46 publications
1
58
2
Order By: Relevance
“…Estimated point mutation rates are also lower in genes that are conserved across most bacteria than in genes conserved in all Streptomyces species. The effects of evolutionary distance and gene data set on inferred mutation rate are stronger in synonymous sites, suggesting widespread fitness effects of synonymous mutations in Streptomyces core genes, as has been shown in a variety of bacteria and eukaryotes (3841). These results suggest that comparisons of evolutionary event rates between bacterial groups can be strengthened through normalizing rates based on evolutionary distance between samples within each group.…”
Section: Discussionmentioning
confidence: 65%
“…Estimated point mutation rates are also lower in genes that are conserved across most bacteria than in genes conserved in all Streptomyces species. The effects of evolutionary distance and gene data set on inferred mutation rate are stronger in synonymous sites, suggesting widespread fitness effects of synonymous mutations in Streptomyces core genes, as has been shown in a variety of bacteria and eukaryotes (3841). These results suggest that comparisons of evolutionary event rates between bacterial groups can be strengthened through normalizing rates based on evolutionary distance between samples within each group.…”
Section: Discussionmentioning
confidence: 65%
“…The distribution of fitness effects of synonymous mutations Previous studies have shown that synonymous mutations can directly affect fitness (e.g., Firnberg et al 2014;Hunt et al 2014;Lind et al 2010) and impact the ability of populations to adapt to new environments (Agashe et al 2016;Bailey et al 2014). For example, Bailey et al (2014) found that two synonymous mutations were responsible for adaptation of Pseudomonas fluorescens to a new medium by increasing the expression of a gene involved in glucose metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Bailey et al (2014) found that two synonymous mutations were responsible for adaptation of Pseudomonas fluorescens to a new medium by increasing the expression of a gene involved in glucose metabolism. In a more recent study in Methylobacterium extorquens, Agashe et al (2016) found that the deleterious effect of synonymous mutations in a medium with methylamine as the sole carbon source could be rescued by different mutations, including four synonymous mutations that increased transcription and protein production levels. The impact of synonymous mutations at the genome-wide level was also found in patterns of codon usage bias (syno-nymous codons are used at different frequencies) across genomes.…”
Section: Resultsmentioning
confidence: 99%
“…However, in our RCS analysis the extent to which mutant RNA structures contained beneficial and not deleterious base-pairings predicted the fitness of synonymous mutants both at the beginning of the gene and far beyond the start codon, augmenting more general predictors based on RNA folding energy and ribosome binding(Salis et al, 2009). The use of gene-specific empirical metrics such as RCS may therefore be useful in cases when general metrics fail to predict the effects of synonymous changes(Agashe et al, 2016; Knöppel et al, 2016). These results can also help to explain biases toward stronger minimum free energy in later gene regions(Gu et al, 2010), since a stronger local fold in later regions of the gene is less likely to interact with upstream RNA structures.…”
Section: Discussionmentioning
confidence: 99%